The Effectiveness of Reality Counseling to Improve Low Self-Concept of Students Age 13-15 of SMP Negeri 3 Banyuwangi - Nuraini, Erina; priawasana, endra (Journal of Education Technology and Inovation, 2023)
Self-concept is a very determining factor in interpersonal communication. This research aims to determine the effectiveness of reality counseling to improve the low self-concept of class VIII students at SMP Negeri 3 Banyuwangi. This study used a quasi-experimental research design, with the Purposive Sampling Area method to determine the research area. Determining the number of respondents, researchers used purposive sampling with a total of 6 students. This study uses the rating scale method (rating scale), interviews and documentation. Based on data analysis using the Wilcoxon test formula, the number is -2.201 with a significant level of <0.05, namely 0.028, thus there is an increase in the self-concept of class VIII students of SMPN 3 Banyuwangi. This shows that reality counseling is effective for improving the self-concept of class VIII students of SMP Negeri 3 Banyuwangi